2016
DOI: 10.1007/s00148-016-0625-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive skills, non-cognitive skills, and family background: evidence from sibling correlations

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 55 publications
(55 reference statements)
1
46
0
1
Order By: Relevance
“…Previous research has shown that individuals with positive control beliefs invest more in their own education (Coleman and Deleire 2003;Hadsell 2010) and in the education of their children (Lekfuangfu et al 2014), and adolescents' control beliefs are associated with parental socioeconomic status (Schurer 2015;Anger and Schnitzlein 2015). Lundborg et al (2015) show evidence on the education-related heterogeneity in the response to health shocks using Swedish administrative data, although the authors do not discuss the mechanisms.…”
Section: Mechanismmentioning
confidence: 89%
“…Previous research has shown that individuals with positive control beliefs invest more in their own education (Coleman and Deleire 2003;Hadsell 2010) and in the education of their children (Lekfuangfu et al 2014), and adolescents' control beliefs are associated with parental socioeconomic status (Schurer 2015;Anger and Schnitzlein 2015). Lundborg et al (2015) show evidence on the education-related heterogeneity in the response to health shocks using Swedish administrative data, although the authors do not discuss the mechanisms.…”
Section: Mechanismmentioning
confidence: 89%
“…With a mean age of 40-42 years in all data sets, the personality traits should mostly be stable. As constant factors, such as genetic determination and family background account for large variation in personality traits (Eysenck, 1990;Riemann et al, 1997;Anger and Schnitzlein, 2017), I expect within-individual variation across time in non-cognitive skills to be a minor problem.…”
Section: Measures Of Personalitymentioning
confidence: 99%
“…Based on the German Socio-Economic Panel Study (SOEP), the results showed that maternal job loss increased preschool children's socio-behavioural problems and decreased adolescents' belief in self-determination. Using data of the locus of control, reciprocity and the Big Five personality traits (openness, conscientiousness extraversion, agreeableness, and neuroticism), Anger and Schnitzlein estimated sibling correlations in non-cognitive skills to evaluate the effect of family background on skill formation, which results showed that the effect was all-around and multifaceted [21]. Using a recent US panel dataset that tracked children between grades K-5, Fletcher and Wolfe presented new evidence of the importance of family income in the formation and evolution of children's non-cognitive skills [22].…”
Section: Family Background and Non-cognitive Skillsmentioning
confidence: 99%